First Records Of Leptoglossus Occidentalis Heidemann, 1910 (Hemiptera: Heteroptera: Coreidae) In Brazil And South Africa - Van Der Heyden, Torsten; Faundez Peña, Eduardo Ivan (My University, 2020)
The first records of Leptoglossus occidentalis for Finland are reported. Information on the distribution of the species in Europe, in particular in its northern part, is summarized.
Keywords: Invasive; Western Conifer Seed Bug; Faunistics; New Records; Citizen Science